2002
DOI: 10.1029/2001jd001108
|View full text |Cite
|
Sign up to set email alerts
|

Two case studies of winter continental‐type water and mixed‐phase stratocumuli over the sea 2. Absorption of solar radiation

Abstract: [1] We have carried out airborne experiments on cloud-radiation interactions for wintertime boundary layer clouds over the East China Sea and the Japan Sea in January 1999 as part of the Japanese Cloud and Climate Study (JACCS) program. By means of collocated and synchronized flights of two instrumented aircraft, flying above and below the cloud layer, respectively, we directly measured the visible and near-infrared (IR) solar absorption for two cases of stratiform clouds: one featuring supercooled water strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The scattering phase functions measured for the first time for mixed‐phase boundary layer cloud will serve as unique and valuable data set for implementation and validation of an iterative method, based on the bi‐component (water and ice crystals) representation of cloud composition, for the retrieving of the microphysical properties. The measured visible and near‐infrared solar absorption is discussed in detail in the companion of this paper [ Asano et al , 2002] with the interpretation of the results from a numerical simulation study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering phase functions measured for the first time for mixed‐phase boundary layer cloud will serve as unique and valuable data set for implementation and validation of an iterative method, based on the bi‐component (water and ice crystals) representation of cloud composition, for the retrieving of the microphysical properties. The measured visible and near‐infrared solar absorption is discussed in detail in the companion of this paper [ Asano et al , 2002] with the interpretation of the results from a numerical simulation study.…”
Section: Discussionmentioning
confidence: 99%
“…The results are attempted to provide some basic information on the structural, microphysical and optical properties with the intention of obtaining some insight into cloud radiative transfer problem and into the inference of cloud composition from satellite information. Subsequent measured visible and near‐infrared solar absorption are discussed with details in the companion of this paper [ Asano et al , 2002] with the interpretation of the results from a numerical simulation study.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements used in the study are based on the in situ angular scattering coefficient measurements performed with the Polar Nephelometer [ Gayet et al , 1997; Crépel et al , 1997]. The experimental data have been obtained during three campaigns, namely, Avion de Recherche Atmosphérique et de Télédétection (ARAT'97) [ Duroure et al , 1998], CIRRUS'98 [ Durand et al , 1998], and the Japanese Cloud and Climate Study (JACCS'99) [ Asano et al , 2002; Gayet et al , 2002a], which were carried out from Clermont‐Ferrand (central part of France), Tarbes (southwest of France), and over the Sea of Japan, respectively. Collectively, these campaigns present the advantage of merging three large sets obtained in a wide variety of meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol particles in Asian outflow are thought to be one of possible major sources of the global INP load and have large impacts on aerosol‐cloud‐precipitation interactions on local, regional, and global scales. For example, aircraft measurements around the Japan Islands by Asano et al (2002) and Gaynet et al (2002) revealed the occurrence of boundary‐layer mixed‐phase clouds at temperatures above −15°C during a wintertime cold‐air outbreak event from the Asian continent (Asano et al, 2002; Gaynet et al, 2002), indicating the existence of certain efficient INPs in Asian continental outflow. Ground‐based in situ and/or lidar measurements in China (Bi et al, 2019), Japan (Isono et al, 1959; Murayama et al, 2001; Sakai et al, 2004), and the United States (Ault et al, 2011; Creamean et al, 2013; Pratt et al, 2009; Sassen, 2002) have suggested the importance of long‐range transported dust particles and/or primary biological aerosol particles (PBAPs) such as fungal spores and bacteria from the Asian continent for heterogeneous ice nucleation and subsequent precipitation processes.…”
Section: Introductionmentioning
confidence: 99%